E-Budget Hira Catering System - Rusli, Normaisarah; Mohd Nawi, Prof Dr Nazri (Applied Information Technology And Computer Science, 2022)
Hira Catering E-Budget System is a web-based system developed to enhance and help increase the efficiency of the existing system and also make the booking process at Hira Catering run more smoothly and efficiently. The booking system used previously is manual. In the context of this system, online booking is much easier than manual. Manually stored data will cause problems in terms of data security and difficulty in retrieving data in the future for reporting purposes. In addition, customers have trouble planning the budget when booking because they do not have an overview of the menu and packages organized for easy understanding. Therefore, the e-budget system has been developed to overcome the shortcomings of the previous system and further improve the booking process at Hira Catering. Hira Catering e-budget system is built using evolutionary prototype model which has five SDLC phases namely planning phase, analysis phase, design phase, prototype phase and implementation phase. This system was developed using PHP as the intermediary discussion and MYSQL as the database. The system consists of several key modules including user registration, login, booking, managing the system and generating reports. In conclusion, the development of this system can improve the productivity of the booking system at Hira Catering more perfectly and easily.